Pendampingan Pencatatan Keuangan dalam Upaya Menjaga Keberlangsungan Usaha di UKM Wisnu Batik - Dwi Anggarani; Irfan Fatoni; Syamsul Bahri (Lembaga Pengembangan Kinerja Dosen, 2025)
This Community Service (PkM) program aims to provide assistance in financial recording and direct involvement in the production process at the Wisnu Batik SME. The main focus of the activity is to support the sustainability of micro-enterprises based on local culture, particularly through improved management and the preservation of traditional values. The activity was carried out for two months in the form of field work practice (PKL), using participatory observation methods, semi-structured interviews, and direct documentation. One of the main results of the activity was the implementation of a quarterly financial recording system based on SIINAS (National Industrial Information System), which has been proven to improve the accuracy and transparency in the preparation of business reports. Furthermore, the direct involvement of the interns in the traditional batik production process provided important insights into the production stages, the cultural values ​​contained, and the challenges faced in maintaining quality and continuity of production. Analysis of the cost of goods manufactured (COGS) and monthly revenues showed that the Wisnu Batik SME has great potential for sustainable development if managed with a more systematic and professional approach. The synergy between good financial management and production process efficiency is an important foundation in strengthening the competitiveness of SMEs in the midst of market competition. This activity also serves as concrete evidence that collaboration between the world of education and MSMEs can encourage positive transformation in micro-business management towards a more modern, measurable, and culturally value-based direction.